Tarantula welfare may be improved with greater environmental complexity: A preliminary behavioral study with Brazilian black tarantulas (Grammastola pulchra) - Stalter, Laura; Dorleus, Tayler; Milone, Nicholas; Sincage, Jamie; Skurski, Michelle; Leeds, Austin (PLOS ONE, 2024)
Increased environmental complexity has positive effects on the welfare status of vertebrates living in human care; however, this line of research has received little focus in invertebrates. Here we conducted a preliminary investigation of Brazilian black tarantula (Grammastola pulchra) behavior in relation to environmental complexity. Using a counterbalanced design, we housed tarantulas in both Standard and Complex environments. Complex housing was differentiated from Standard by being approximately six times larger and containing six times as many structural elements. We evaluated (1) how does tarantula behavior differ between these two housing conditions, (2) does housing affect tarantula behavior in a novel environment test, and (3) do tarantulas prefer one housing condition over the other? Activity budgets were approximately equivalent between the two housing conditions with inactivity accounting for nearly all observed behavior. Home ranges and core areas were 77% and 113% larger in the Complex housing condition. When in a novel environment, tarantulas had 150% greater odds of being active after living in the Complex condition. Interestingly, the tarantulas showed no clear preference for either environment in the preference test. Our preliminary results suggest tarantula welfare may be improved with greater environmental complexity as demonstrated through more neophilic response to novelty and greater home range and core area size when living in Complex housing. However, it is worth noting that broad patterns of behavior were similar, no clear preference in housing was identified, and our study sample size was limited. Further research is needed to better understand the behavior and welfare of tarantulas, but this study demonstrates how established methodologies used in the study of vertebrates can be readily applied to invertebrates.